Full structural dynamic response from ambient vibration of Giotto's bell tower in Firenze (Italy), using modal analysis and seismic interferometry. (March 2019) - Lacanna, G.; Ripepe, M.; Coli, M.; Genco, R.; Marchetti, E.
Abstract: The preservation of historical buildings mainly depends on our capacity to monitor their ageing and quickly detect potential damage. We show how the dynamic characteristics of a building (i.e., frequency, shapes mode and seismic wave velocity) can be automatically identified and tracked in real-time by combining modal analysis with seismic interferometry. The assessment of these characteristics is performed on Giotto's bell tower in Firenze, Italy, by installing a temporary network of seismic sensors. The natural frequencies and modal shapes of the structure are calculated by enhanced frequency domain decomposition (EFDD). The impulse response functions estimated by following a waveform deconvolution approach are analysed to investigate the seismic wave dispersion in Giotto's bell tower. We show that Giotto's bell tower is a dispersive structure affected by a bending deformation, with a weak contribution from soil-system interaction. Combining the results of operational modal analysis (OMA) and seismic interferometry from the same ambient noise recording provides a unique and complete dynamic response of important monuments such as Giotto's bell tower.